Strategi Meningkatkan Brand Image dan Daya Saing Dalam Pemasaran Jasa Di Perguruan Tinggi - Aynun Nurul Ulufah; Prim Masrokan Mutohar; Agus Eko Sujianto (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Islamic Higher Education Institutions to be able to compete among other educational institutions, both public and private, must transform by looking for formulations and innovations according to the superior character of each institution. With marketing strategies, universities can build public perceptions and assumptions to improve the reputation and positive brand image of universities. This research aims to reveal strategies to improve brand image and competitiveness in marketing at Darussalam Gontor University College. This research uses a qualitative approach. Data collection was carried out using interview, observation and documentation techniques. The research results show that: (1) UNIDA Gontor marketing segmentation strategy includes identifying and measuring market segments; (2) UNIDA Gontor marketing targeting strategy to increase its brand image so that it is competitive includes: concentrated targeting, multisegment targeting referrals with superior higher education boarding school systems, international achievements and reputation as well as building alumni and (3) Higher education marketing promotion strategies to improve brand image and UNIDA Gontor competitiveness uses conventional media including: brochures, articles, magazines and non-conventional media, namely direct marketing such as websites, social media applications such as Facebook, Instagram, Twitter and YouTube.